2020
DOI: 10.5483/bmbrep.2020.53.6.060
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and vasculogenic mimicry as therapeutic targets in ovarian cancer

Abstract: Tumor angiogenesis is an essential process for growth and metastasis of cancer cells as it supplies tumors with oxygen and nutrients. During tumor angiogenesis, many pro-angiogenic factors are secreted by tumor cells to induce their own vascularization via activation of pre-existing host endothelium. However, accumulating evidence suggests that vasculogenic mimicry (VM) is a key alternative mechanism for tumor vascularization when tumors are faced with insufficient supply of oxygen and nutrients. VM is a tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 83 publications
0
35
0
1
Order By: Relevance
“…In theory, chemotherapy or targeted therapy combined with anti-VM should be a good strategy for this kind of disease. However, at present, anti-VM only stays at the stage of preclinical pharmacology and early clinical research, and there is no reliable evidence to support anti-VM [ 38 ]. It is expected that more research will focus on this field, so that anti-VM combined with current strategies can bring promising benefits to such patients.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, chemotherapy or targeted therapy combined with anti-VM should be a good strategy for this kind of disease. However, at present, anti-VM only stays at the stage of preclinical pharmacology and early clinical research, and there is no reliable evidence to support anti-VM [ 38 ]. It is expected that more research will focus on this field, so that anti-VM combined with current strategies can bring promising benefits to such patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies provide evidence that VM serves as a key alternative process for tumor neovascularization under an insufficient blood supply of oxygen and nutrients to the tumor tissue. VM is an alternative tumor vascularization mechanism that is directly built inside tumor cells to provide them with nutrients, which differs from angiogenesis via activation of the pre-existing host endothelium [ 10 , 11 , 39 ]. Thus, VM targeting may represent a promising therapeutic strategy and overcome the limitations of anti-angiogenic treatment of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vasculogenic mimicry (VM) refers to a blood supply system that is formed in the tumor cells themselves, and not by vascular endothelial cells, such as in angiogenesis. These systems appear in malignant tumors and contribute to an aggressive disease, rapid tumor growth, and a poor prognosis [ 8 , 9 , 10 , 11 ]. It has been identified that various factors can regulate VM, including vascular endothelial cadherin, ephrin type-A receptor 2, focal adhesion kinase, extracellular signal-regulated kinase, and matrix metalloproteinase (MMP) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations